2016
DOI: 10.1016/j.bbmt.2015.11.360
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Use of Allogeneic Hematopoietic Cell Transplantation (HCT) in Patients Age 70 Years and Older: A CIBMTR Study of Trends and Outcomes

Abstract: Limited data exist regarding the use and outcomes of allogeneic HCT in adults 70 years and older. We aimed to describe trends and outcomes of allogeneic HCT in this population utilizing data reported to the CIBMTR from 2000-2013 from US centers. 1106 allogeneic HCT recipients 70 years (89% 70-74, 10% 75-79, <1% 80) from 103 centers are included. The most common disease indications were AML (54%), MDS/MPN (22%), and NHL (10%). 82% had KPS 80% and 46% had HCT-CI 3 (HCT-CI capture began in 2008). Unrelated donor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Patients 60 to 74 years of age achieved a favorable 2-year survival rate of 48% and a low nonrelapse mortality (NRM) rate of 14%. Registry data for AML and myelodysplastic syndrome patients 70 years and older using all donor sources and conditioning regimens showed 2-year survival rate of 38% and 2-year NRM rate of 30% [55]. Haploidentical and umbilical cord graft studies in older AML patients have been described [60][61][62].…”
Section: Older Age and Allogeneic Transplant For Amlmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients 60 to 74 years of age achieved a favorable 2-year survival rate of 48% and a low nonrelapse mortality (NRM) rate of 14%. Registry data for AML and myelodysplastic syndrome patients 70 years and older using all donor sources and conditioning regimens showed 2-year survival rate of 38% and 2-year NRM rate of 30% [55]. Haploidentical and umbilical cord graft studies in older AML patients have been described [60][61][62].…”
Section: Older Age and Allogeneic Transplant For Amlmentioning
confidence: 99%
“…The Center for International Blood and Marrow Transplant Research (CIBMTR) showed 22% of allogeneic transplant recipients were 60 years or older in 2007 to 2013 among common malignant conditions [54]. Likewise, US allografts for patients 70 years and older have risen 10-fold over the past decade, with AML as the leading indication ( Figure 1) [55]. Few older AML patients receive allogeneic transplant; a population study of AML diagnosed between 2000 and 2007 showed only 4% of AML patients 65 to 74 years underwent allografts [56].…”
Section: Older Age and Allogeneic Transplant For Amlmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Patients in their 8th decade of life now represent the area of fastest growth of allogeneic and autologous grafts, and can have reasonable outcomes. 6,7 The European registry showed that from 2006 to 2010, autografts for myeloma in those $70 years represented 3% of transplants compared with only 1.1% a decade before. 7 Similarly, Muffly et al reported in abstract form that 3.3% of allogeneic HCTs in 2012 and 2013 derived from this age group vs 0.4% the decade before.…”
Section: Older Age and Transplant Utilizationmentioning
confidence: 99%
“…7 Similarly, Muffly et al reported in abstract form that 3.3% of allogeneic HCTs in 2012 and 2013 derived from this age group vs 0.4% the decade before. 6 Common transplant indications of MM, non-Hodgkin lymphoma, AML, and MDS peak in older adults and yet transplant is infrequently offered to patients $60 years. Oran and Weisdorf estimated among patients $65 years with AML, 2.4% underwent HLA typing and 0.8% pursued allografts.…”
Section: Older Age and Transplant Utilizationmentioning
confidence: 99%